A New Type of Li Deposit: Hydrothermal Crypto-Explosive Breccia Pipe Type - Jiang, Shao-Yong; Su, Huimin; Zhu, Xinyou; Zhu, Kangyu; Duan, Zhenpeng (Journal of earth science (Wuhan, China), 2022)
Lithium is one of the important strategic energy metals, which is in short supply in China. There are three major types of lithium deposits: brine and salt lake type, highly differentiated granite or pegmatite type, and carbonate-clay type. In recent years, some new types of lithium deposits have also begun to receive great attention and subject recent research. There are many crypto-explosive breccia pipe type deposits in the world, including copper, gold, lead, zinc, tungsten and tin deposits, but little is known about this type of lithium deposit. This paper introduces the latest research results of the Weilasituo Sn−Li−Rb polymetallic deposit in Inner Mongolia (NE China), which occurs in the middle-southern section of the Great Xing’an Range metallogenic belt. A remarkable feature of this deposit is the coexistence of various mineralization types, including granite type Rb and Sn−Zn, hydrothermal crypto-explosive breccia pipe type Li−Rb, quartz vein type Sn−Zn and sulfide vein type Pb−Zn−Ag mineralization. Among them, hydrothermal crypto-explosive breccia pipe type Li-Rb deposit is currently very rare at home and abroad, which is likely a new type of rare metal deposit that worthy of our attention. This paper systematically summarizes the geology, alteration and mineralization, geochemistry, isotopes and geochronology of the Weilasituo deposit, and establishes a new petrogenic and metallogenic model.